Optimized preparation of electrospun polyvinyl alcohol - gelatin nanofibers using the Taguchi method - Ramis, Jopeth M. (College of Engineering, University of the Philippines Diliman, 2015)
This study reports the preparation of electrospun polyvinyl alcohol-gelatin (PVAG) nanofibers optimized for the smallest average diameter and size standard deviation with minimum occurence of beading ang splattering. The experiments are performed using the Tagachi method of considering the effect of polymer composition (PVAG ration and solvent ratio of water, formic acid, and acetic acid H2O:FA:HAc) and process factors (tip-to-collector distance TCD and solution flow rate) on fiber morphology. Fiber morphology is measured in terms of four responses: average fiber diameter, standard deviation of fiber diameter, occurence of beading, and occurence of splattering. Analysis of variance and Tukey's test indicate PVAG ration as a main factor affecting standard deviation of fiber diameter and occurence of beading, while solvent ratio significantly influences the average fiber diameter, size standard deviation, and beading probability. TCD affects both average fiber diameter and size deviation, while flow rate only affects the occurence of splattering. Maximum overall desirability for electrospinning PVAG nanofibers at smallest average diameter and size deviation (26.1± 10 nm) with chance of moderate beading and slight splattering was predicted to be at PVAG mass ratio 6.5:3.5, H2O:FA:HAc solvent volume ratio 4:4:2, TCD of 12.5 cm, and flow rate of 1mL/h. Results of confirmatory run agreed with the predicted factor levels at maximum desirability, with average fiber diameter and standard deviation measured to be 26.95 ± 6.39 nm. Electrospun PVAG nanofibers from the confirmatory run are also both bead- and splatter-free. FTIR analyses confirm the presence of both PVA and gelatin, and QCM studies indicate the unique degradation of nanofibers in aqueous environment. Results suggest the application fo Taguchi method may offer a robust and rapid approach for deriving the conditions for production of new and high-quality nanofibers for tissue engineering scaffolds